PPN & PPNBM: SUBJEK, OBJEK SERTA MEKANISME DI INDONESIA - Elvina Zailanty Harahap; Muhammad Hafizhan Fakhri, Ocha Pratika, Dini Vientiany (CV. ADIBA AISHA AMIRA, 2024)
The aim of the research is to increase information regarding VAT and PPnBM. This research uses descriptive research with a qualitative approach. VAT is a tax on consumption of goods and services in the customs area which is imposed in stages in each production and distribution channel. PPnBM is a tax levied on the delivery of BKP which is a luxury item. The VAT rate is regulated as follows: 10% .0%, specifically VAT on exports of Taxable Goods. The PPnBm rate is set at a minimum of 10% and a maximum of 200%. The basis for PPnBM is based on Law Article 8 No. 42 of 2009 concerning the 3rd Amendment to Law no. 8 of 1983